Appropriate Weight Gain During Pregnancy - Stephanie Allen; Linda Bobroff (EDIS)
"Many people these days are concerned about weight gain. Pregnant women often share these concerns; however, it's important for pregnant women to understand that weight gain during pregnancy is critical to their babies' health." This 2-page Family Album Radio transcript was written by Stephanie Allen and Linda Bobroff, and published by the UF Department of Family, Youth and Community Sciences, August 2012.